Motivasi dan Partisipasi Peternak dalam Pengembangan Ternak Kerbau di Kabupaten Pandeglang (Studi Kasus: Desa Cibarani Kecamatan Cisata) (The Motivation and Participation of Farmers in the Farming Development Buffaloes in Pandeglang District (Case Study : Cibarani Village Cisata Sub-District)) - Arfiani Arfiani; Asnath Maria Fuah; Bagus Priyo Purwanto (IPB University, 2015)
Buffalo’s population decreased for 0.06% every year in 2005 to 2013 in Pandeglang District. Development programs and activities were supported by the local government policy in order to overcome the problems. Farmers as the main human resources play important roles in buffaloes farming development. This research was conducted to assess the knowledge and skills, motivation and participation of farmers in buffaloes farming development in Pandeglang District, using the study case in Cibarani Village, Cisata Sub-district. Surveys and interview to 93 farmers were used to obtain the data required in the study. Farmers were divided into four farmer groups i.e. Saluyu Jaya, Cirukap Makmur, Taruna Mandiri and Putra Makmur with the number of respondents were 16, 10, 21 and 46 respectively. Data were analyzed descriptively and provided in tables. Level of knowledge, motivation and participation of human resources were analyzed using a Mann-Whitney non-parametric statistics. The results showed that the farmer’s knowledge and participation were on satisfactory level, while their motivations, in keeping buffaloes farming as their main activities, were high.Keyword : buffalo, farmer, knowledge, motivation, participation